ANALISIS ARUS JENUH DAN PANJANG ANTRIAN SIMPANG BERSINYAL PADA PERSIMPANGAN ANGKATAN 66 KOTA PALEMBANG - Rhaptyalyani, Rhaptyalyani; Sitanggang, Baru Monang; Arliansyah, Joni (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The increasing population of the city of Palembang per year reaching 1.95 % thus making the high value of saturation flow , queue length , and delay at intersection is a factor causing traffic jam and needed to solve. This study discussed about saturated flow analysis and long queue at intersections for existing and next 5 years. The analysis results showed Angkatan 66 intersection having level of service in the range F. Scenarios are making for increase the level of service in the intersection, first scenario; resetting traffic light time in intersection, second scenario; change the width of roads geometric, third scenario; fly over planning. From the scenarios, showed that the third one gave the best solution to reduce saturation flow, queue length and delay in Angkatan 66 intersection.